Impaired Cerebellum to Primary Motor Cortex Associative Plasticity in Parkinson’s Disease and Spinocerebellar Ataxia Type 3 - Lu, Ming-Kuei; Chen, Jui-Cheng; Chen, Chun-Ming; Duann, Jeng-Ren; Ziemann, Ulf; Tsai, Chon-Haw (Frontiers in Neurology, 2017)
Background Functional perturbation of the cerebellum-motor cortex (M1) interactions may underlie pathophysiology of movement disorders such as Parkinson’s disease (PD) and spinocerebellar ataxia type 3 (SCA3). Recently M1 motor excitability can be bidirectionally modulated in young subjects by corticocortical paired associative stimulation (PAS) on cerebellum and contralateral M1 with transcranial magnetic stimulation (TMS), probably through the cerebello-dentato-thalamo-cortical (CDTC) circuit. In this study, we investigated the cerebellum to M1 associative plasticity in healthy elderly, PD and SCA3. Methods Ten right-handed PD patients, nine gene-confirmed SCA3 patients and ten age-matched healthy controls (HC) were studied. One hundred and twenty pairs of TMS of the left M1 preceded by right lateral cerebellum (CB) TMS at an interstimulus interval of 2 ms (CB-M1 PAS2ms) and 6 ms (CB-M1 PAS6ms) were respectively applied with at least one week interval. M1 excitability was assessed by motor-evoked potential (MEP) amplitude, short-interval intracortical inhibition (SICI), intracortical facilitation (ICF) and cerebellar inhibition (CBI) at the first dorsal interosseous muscle of the right hand before and after the CB-M1 PAS. Results The M1 excitability represented by MEP amplitude was significantly facilitated and suppressed in the HC group by CB-M1 PAS2ms and CB-M1 PAS6ms, respectively. The bidirectional modulation on MEP amplitude was absent in the PD and SCA3 groups. SICI and the baseline CBI were significantly reduced in the SCA3 group compared to those of the HC group irrespective of the CB-M1 PAS protocols. There was a significant reduction of CBI immediately and 60 minutes after the CB-M1 PAS protocols in the HC group but not in the patient groups. No significant change of ICF was found. Conclusions Corticocortical CB-M1 PAS can induce bidirectional motor cortical plasticity in M1 for healthy aged subjects. The modulation may be independent of the inhibitory neurocircuits such as SICI and CBI and the facilitatory mechanism like ICF. Both patients with PD and SCA3 showed impairment of such plasticity, suggesting significant functional perturbation of the CDTC circuit.